Information technology policy and the digital divide : lessons for developing countries - Tsuji, Masatsugu; Kagami, Mitsuhiro; Giovannetti, Emanuele (Cheltenham, UK ; Northhampton, MA : Edward Elgar Pub., 2004)
This book compares the advantages and diadvanges of the IT resolution through detailed studies of a variety of developed and developing nations and regions: Argentina, Estonia, the EU, India, Japan, Korea, Mexico, South Africa, Thailand and the USA.
Includes bibliographical references and index.
aug 06/06/13
Loans
Keywords: Information technology -- Government policy; Information technology -- Government policy -- Developing countries